ADAMTS-1, a multifunctional proteinase, in the uterus of both estrous cycle rats and ovariectomized rats can be regulated via hormones - Ak, Tuba Parlak; Yaman, Mine; Bayrakdar, Ali; Bulmus, Ozgur (Springer, 2025)
Remodeling of the extracellular matrix (ECM) throughout the estrous cycle is one of the most striking features of the uterus. A disintegrin and metalloprotease with thrombospondin type I motifs (ADAMTS-1) is a metalloproteinase responsible for the degradation of some proteoglycans, which are ECM components. In this study, ADAMTS-1 distribution was analyzed in the uterus of ovariectomized rats administered 17 beta-estradiol (E2) and progesterone (P4) and in the uterus at different estrous stages. Ovariectomized (OVX) rats were subjected to single and combined E2 (0.2 mg/kg) and P4 (10 mg/kg) hormone replacement therapies. E2 was administered for 3 consecutive days, followed by E2, P4, or E2 + P4 for 4 consecutive days. The serum level of E2 decreased from the proestrus phase to the diestrus phase, but that of P4 was the highest in the estrus phase. During the estrus phase, the serum level of luteinizing hormone (LH) was the lowest and that of follicle-stimulating hormone (FSH) was the highest. P4 level increased significantly in the OVX + P4 and OVX + E2 + P4 groups compared with the OVX group. The serum levels of LH and FSH decreased in the OVX + E2 and OVX + P4 groups compared with the OVX group, and were the lowest in the OVX + E2 + P4 group. ADAMTS-1 immunoreactivity in luminal, glandular, and stromal cells of the uterus decreased from proestrus to diestrus. When immunoreactivity in hormone replacement groups was compared, weak immunoreactivity was observed in the OVX group. ADAMTS-1 immunoreactivity gradually increased in OVX + P4 and OVX + E2 groups, and was particularly notable in luminal, glandular, and stromal cells in the OVX + E2 + P4 group. ADAMTS-1 distribution was affected by the estrous cycle process and hormone replacement therapy in the OVX procedure.
Keywords: ADAMTS-1; Estrous cycle; Ovariectomy; Rat uterus